Factors Influencing Customer Risk Perception of iB Mudharabah Deposits at PT. Bank Sumut KCPSy Hamparan Perak - Santi Arafah; Yunanda Eka Putra; Saparuddin Siregar; Sugianto (Department of Islamic Economics, Faculty of Islamic Religion, Yudharta University Pasuruan, East Java, Indonesia., 2026)
Purpose: This research examines the effect of Sharia financial literacy, trust, and transparency on customer risk perception of iB Mudharabah deposit products at PT Bank Sumut KCPSy Hamparan Perak. Design/Methodology/Approach: A quantitative cross-sectional approach was applied using questionnaires distributed to 100 iB Mudharabah deposit customers selected through purposive sampling. Data were measured using a five-point Likert scale and analyzed using SEM-PLS, including outer and inner model testing. Findings: Sharia financial literacy, trust, and transparency have a positive and significant effect on customer risk perception. The adjusted R-square value of 0.670 indicates that 67% of the variation in risk perception is explained by these variables. Practical Implications: The findings suggest that customer-based risk mitigation requires strengthening Sharia financial literacy, enhancing trust, and ensuring transparency in mudharabah deposit products. Originality/Value: This research contributes to Sharia banking literature by highlighting customer risk perception in regional Sharia banks and emphasizing behavioral and relational factors in mudharabah-based risk management.